Astacoides hobbsi, a new crayfish (Crustacea: Decapoda: Parastacidae) from Madagascar - Boyko, Christopher B.; Ravoahangimalala, Olga Ramilijaona; Randriamasimanana, Désiré; Razafindrazaka, Tony Harilala (Zootaxa, 2005)
A new species of crayfish, Astacoides hobbsi, is the seventh recognized in the endemic Madagascan genus Astacoides Guérin-Méneville, 1839 and is described from four male specimens collected in the Andranofotsiorana effluent of the river Ranomadio (Fianarantsoa province). The new species can be distinguished from all congeners by a combination of limited carapace spination, pale white color, gill formula of 13 + epr + 5r, lack of bullar lobes on sternite XIII, laterally curved lateral processes on sternite XIII, and spination of third maxilliped merus and ischium. The new species co-occurs with three other Astacoides species (A. granulimanus Monod & Petit, 1929, A. caldwelli (Bate, 1865), and A. betsileoensis Petit, 1923) in the same stream system. Special consideration should be given to conservation of this new species, as it is the Astacoides species known from the fewest specimens and may have a very restricted distribution.